2019
DOI: 10.1016/j.jtcvs.2019.01.134
|View full text |Cite
|
Sign up to set email alerts
|

Transplant arteriosclerosis in humanized mice reflects chronic lung allograft dysfunction and is controlled by regulatory T cells

Abstract: Objective: Chronic lung allograft dysfunction (CLAD) is a severe complication of lung transplantation limiting long-term survival. We studied correlations between CLAD after clinical lung transplantation and leukocyte-mediated development of transplant arteriosclerosis (TA) in a humanized mouse model. The pericardiophrenic artery was procured from surplus tissue of donor lungs (n ¼ 22) transplanted in our clinical program and was implanted into the abdominal aorta of immune-deficient mice.Methods: Allogeneic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…They demonstrated that a subpopulation of Tregs (CD4 + CD25 high CD127 low ) in the blood early after lung transplantation were responsible for a protective effect against chronic lung allograft dysfunction (CLAD), mortality, and the need for re‐transplantation . This study reinforced the findings of their prior in vitro and in vivo studies, which showed a pivotal role for Tregs in the regulation of immune cells that had a large impact on long‐term outcomes after lung transplantation .…”
supporting
confidence: 66%
“…They demonstrated that a subpopulation of Tregs (CD4 + CD25 high CD127 low ) in the blood early after lung transplantation were responsible for a protective effect against chronic lung allograft dysfunction (CLAD), mortality, and the need for re‐transplantation . This study reinforced the findings of their prior in vitro and in vivo studies, which showed a pivotal role for Tregs in the regulation of immune cells that had a large impact on long‐term outcomes after lung transplantation .…”
supporting
confidence: 66%
“…In comparison with effector T cells, the mechanisms of action of Treg have been investigated only recently . Moreover, few clinical studies have evaluated the relationship between Treg and outcomes after lung transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, histological changes in the artery were associated with development of chronic lung allograft dysfunction in the patient, indicating the presence of alloreactive T cells at time of transplant. 225 Such models could provide a method for developing customized patient-specific therapies.…”
Section: Perspectivesmentioning
confidence: 99%